Epidermal growth factor receptor (EGFR) overexpression in endometrial carcinoma: association with histopathologic parameters - Atif Ali Hashmi; Zubaida Fida Hussain; Muhammad Irfan; Maheen Naeem; Shumaila Kanwal Hashmi; Huda Asif; Samina Baloch; Naveen Faridi (BMC, 2019)
Abstract Background Epidermal growth factor receptor (EGFR) is a cellular oncoprotein which is overexpressed in many human cancers including a subset of endometrial cancers. Immunohistochemical (IHC) expression of EGFR has been investigated in previous studies; Role of EGFR in endometrial carcinoma as a prognostic biomarker has not been studied in our population; therefore we aimed to evaluate the expression of EGFR in cases of endometrial carcinoma in loco-regional population and its association with histologic variables. Methods Total 89 cases of endometrial carcinoma were selected from records of pathology department archives. All patients underwent surgeries at Liaquat National hospital, Karachi from January 2012 till December 2017 over a period of 6 years. Slides of all cases were retrieved and reviewed by two senior histopathologists and pathologic characteristics were evaluated. Moreover, representative tissue blocks of all 89 cases were selected for EGFR immunohistochemistry. Results 73% (65 cases) showed no EGFR expression, while 21.3% (19 cases) showed low EGFR expression and 5.6% (5 cases) revealed high EGFR expression. Significant association of EGFR expression was noted with histologic type. Serous carcinoma and carcinosarcoma showed high expression of EGFR. On the other hand, no significant association of EGFR with other histopathologic parameters was found. Conclusion Overall, we found a low EGFR expression in endometrial carcinoma in our population without any significant pathological association except for its high expression in serous carcinoma and carcinosarcoma; however, more large scale studies are warranted to validate these findings.